Awarding college credit for MOOCs: The role of the American Council on Education - Stone, Jason E (Education Policy Analysis Archives, 2016)
Emerging alongside the open educational resources movement of the past decade, Massive Open Online Courses (MOOCs) have been widely heralded as advancing cause of providing increased access to higher education. The article explores the implications of the recommendation by the American Council on Education (ACE) to offer college credit for a select group of MOOC offerings, with regard to benchmarks of access and affordability, in light of recent developments in credentialing. In particular, the article examines the innovative partnership between Arizona State University’s Global Freshman Academy (GFA) and MOOC provider edX, with regard to its potential to both disrupt and transform higher education by contributing to the development of accessible, affordable, alternative credentialing pathways.